Genetic Study In a Pakistani Family Reveals Autosomal Recessive Type of Artemis Deficiency - Saddaf Ayub; Abeerah Zainub; Nida Shafi; Zara Khalid Khan; Lubna Siddique; Syed Irfan Raza (Journal of Rawalpindi Medical College)
Objective: To perform clinical and genetic investigations in two patients suffering from Artemis deficiency with total deficiency of T-B- lymphocytes.